Peningkatan Efektivitas Kerja Guru Melalui Penguatan Supervisi Kepala Sekolah Dan Motivasi Berprestasi - Deden Sumiarsa (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to find efforts that can be made in order to increase the effectiveness of teacher work through a study of its relationship with Principal Supervision and Achievement Motivation. The population of this study amounted to 160 teachers, with a sample of 106 teachers in the KKG Cluster 1, Cibeureum sub-district, Sukabumi City, which was determined using the Slovin formula with an error tolerance of 5%. Data were collected using an instrument in the form of a questionnaire and analyzed by descriptive and inferential statistical analysis.The results showed three positive and significant relationships. First, there is a positive and significant relationship between Principal Supervision and Teacher Work Effectiveness with a correlation coefficient of 0.565. Second, there is a positive and significant relationship between Achievement Motivation and Teacher Work Effectiveness with a correlation coefficient of 0.595. Third, there is a positive and significant relationship between Principal Supervision and Achievement Motivation together with Teacher Work Effectiveness with a correlation coefficient value of 0.680.